Silicene spintronics — A concise review*Project supported by the National Natural Science Foundation of China (Grant Nos. 11274016 and 11474012), the National Basic Research Program of China (Grant Nos. 2013CB932604 and 2012CB619304), and a National Science Foundation (Grant No. 1207141). (August 2015) - Wang, Yang-Yang; Quhe, Ru-Ge; Yu, Da-Peng; Lü, Jing
Abstract Spintronics involves the study of active control and manipulation of spin degrees of freedom in solid-state systems. The fascinating spin-resolved properties of graphene motivate numerous researchers to study spintronics in graphene and other two-dimensional (2D) materials. Silicene, the silicon analog of graphene, is considered to be a promising material for spintronics. Here, we present a review of theoretical advances with regard to spin-dependent properties, including the electric field- and exchange field-tunable topological properties of silicene and the corresponding spintronic device simulations.